2015
DOI: 10.1007/s12640-015-9571-7
|View full text |Cite
|
Sign up to set email alerts
|

Alterations of Bio-elements, Oxidative, and Inflammatory Status in the Zinc Deficiency Model in Rats

Abstract: Our previous study showed that dietary zinc restriction induces depression-like behavior with concomitant up-regulation of the N-methyl-d-aspartate receptor (NMDAR). Because metal ions, oxidative stress, and inflammation are involved in depression/NMDAR function, in the present study, bio-elements (zinc, copper, iron, magnesium, and calcium), oxidative (thiobarbituric acid-reactive substances; protein carbonyl content), and inflammatory (IL-1α, IL-1β) factors were measured in serum, hippocampus (Hp), and prefr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 79 publications
2
20
0
Order By: Relevance
“…From a mechanistic standpoint, we have previously shown that dietary Zn restriction in rats reduced the levels of this microelement in the serum, Hp, and PFC of rats. The reduction was accompanied by increased glutamate release in the PFC after KCl stimulation [19][20][21]41]. Since Zn blocks NMDAR and is crucial for the proper functioning of glutamatergic/zincergic neurons in the hippocampus and PFC [34][35][36][37]42], we wanted to find out whether Zn depletion has an impact on the antidepressant response of glutamate-based atypical compounds.…”
Section: Discussionmentioning
confidence: 99%
“…From a mechanistic standpoint, we have previously shown that dietary Zn restriction in rats reduced the levels of this microelement in the serum, Hp, and PFC of rats. The reduction was accompanied by increased glutamate release in the PFC after KCl stimulation [19][20][21]41]. Since Zn blocks NMDAR and is crucial for the proper functioning of glutamatergic/zincergic neurons in the hippocampus and PFC [34][35][36][37]42], we wanted to find out whether Zn depletion has an impact on the antidepressant response of glutamate-based atypical compounds.…”
Section: Discussionmentioning
confidence: 99%
“…They demonstrated that rats fed with low zinc diet had higher protein carbonyl concentrations. Doboszewska et al investigated effects of zinc deficiency on oxidative factors (thiobarbituric acidreactive substances; protein carbonyl content) in serum, hippocampus, and prefrontal cortex of rats. They showed that zinc deficiency resulted in enhancement of oxidative parameters in the mentioned tissues.…”
Section: Zinc Deficiency Motivates Ages Inducing Conditionsmentioning
confidence: 99%
“…Moreover, zinc deficiency affects the incidence of inflammatory processes by influencing interleukin (IL)-1β production. This element also helps to reduce oxidative stress that leads to neurodegeneration and cell death in the nervous system [42,44].…”
Section: Discussionmentioning
confidence: 99%